A comparative Analytical Studies on Acaciapolyacantha gum Samples collected from three different locations in Sudan - Elhenawy, Ahmed; A. Omer, Elgaili.; A. Alomari, Abdulaziz.; E. Osman, Mohammed. (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2014)
Acacia polyacanthagum(Kakamut gum) samples were collected as natural exudates, from three different locations in Sudan named Abugarin, Gargadah and Layoon forest. Physicochemical properties of gum samples were studied (moisture , ash ,nitrogen , protein, specific rotation, intrinsic viscosity , refractive index, equivalent weight, pH , uronic acid and reducing sugars . Results showed significant differences within each location in most parameters studied, refractive index values were found to be constant in all samples (1.3337) . The effect of location on the properties of gum samples was studied and the analysis showed generally insignificant difference (p 0.05) in all properties studied, except moisture and uronic acid showed significant differences. The general characteristics of Acacia gum might be described as a mean value of all properties studied of all gum samples of the three different locations as follows ; 8.3% moisture, 2.9% ash ,0.35%nitrogen, 2.30% protein,-16.8 specific rotation,10.3ml/g intrinsic viscosity, 4.9 pH , 1348.68 equivalent weight,14.5%uronic acid, 1.3337 refractive index and 0.20%reducing sugar . UV absorption spectra of gum samples were determined and the maximum absorption points were found the same ranging between wavelength (208 and 211nm) . The cationic composition of gum samples was also determined and the results showed that sodium(43.075ppm) has the highest value in all samples followed by iron(27.667ppm) ,zinc(14.297ppm),nickel (4.650ppm), copper (4.025), manganese (2.645ppm), calcium (1.284ppm) and trace amount of lead(0.667ppm), potassium (0.344ppm) and magnesium (0.274ppm). Accordingly, these parameters, therefore, cannot be recommended as qualifying indices.